Boardroom Strategies: How Governance Structures and Firm Size Influence Accounting Conservatism - Vista Yulianti; Dian Sulistyorini Wulandari; Satinah Satinah (PT. Banjarese Pacific Indonesia, 2024)
This study explores the intricate relationship between corporate governance mechanisms—specifically Board Directors, Independent Commissioners, and the Audit Committee—and Accounting Conservatism, focusing on the moderating effects of Firm Size. The findings reveal that Board Directors have a statistically significant impact on Accounting Conservatism, primarily through their ability to provide oversight and challenge aggressive financial practices. However, the influence of Board Directors is moderated by Firm Size, as larger organizations often exhibit complexities that dilute their effectiveness. Similarly, the study underscores the pivotal role of Independent Commissioners in promoting conservative accounting practices. However, their impact is not amplified by Firm Size. The pressures faced by larger firms can lead to more aggressive financial reporting, thereby limiting the effectiveness of Independent Commissioners. Additionally, the Audit Committee is identified as a crucial governance mechanism in fostering Accounting Conservatism, but its effectiveness is also diminished in larger firms due to complex organizational structures. Overall, the research underscores the critical need for governance frameworks to be adaptive and tailored to the unique challenges posed by Firm Size. By recognizing and addressing these complexities, organizations can enhance the integrity and transparency of their financial reporting, thereby fostering trust among stakeholders and contributing to corporate accountability.